View of Vienna - Blaschke, Janos (engraver):::Creator::::::::::::; Schütz, J. B. (Joseph Baptist) (author):::Contributor:::::::::::: (Vienna; Austria; Anton Doll)
Engraving with a panoramic view of Vienna